2000
DOI: 10.1038/sj/ijo/0801285
|View full text |Cite
|
Sign up to set email alerts
|

True

Abstract: Central obesity is the subfraction which carries most of the risks for comorbidities. In this overview we suggest that this is due to neuroendocrine perturbations, where the hypothalamic ± pituitary ± adrenal (HPA) axis assumes a central role. The HPA axis is stimulated by central factors, which are often called stress. This is followed by discrete, periodical elevations of cortisol secretion during every day conditions. Such observations require diurnal measurements under undisturbed conditions. Saliva cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Hypocortisolism also seems more common in women than in men, although its presence has been reported in a subset of men with metabolic syndrome [40]. It has been suggested that hypocortisolism may be a protective response to reduce the damaging effects of the glucocorticoid response to daily hassles, albeit at the expense of symptoms such as high stress sensitivity, pain, and fatigue [41].…”
Section: Resultsmentioning
confidence: 99%
“…Hypocortisolism also seems more common in women than in men, although its presence has been reported in a subset of men with metabolic syndrome [40]. It has been suggested that hypocortisolism may be a protective response to reduce the damaging effects of the glucocorticoid response to daily hassles, albeit at the expense of symptoms such as high stress sensitivity, pain, and fatigue [41].…”
Section: Resultsmentioning
confidence: 99%